Disruption of Budget Rules in the Legal System of the Country: Preemptive Clarification as a Solution (A Case Study of the Budgets from 2020 to 2023) - Mohammad Barzegar Khosravi; Aminollah Paknejad; Amirhosein Bamati Toosi (دانش حقوق عمومی)
Budget Laws in Iran consist of provisions (the single article and notes) and figures (tables and appendices). Clause 9 of the General Policies of the Legislative System, issued on 6/7/1398, mandates adherence to the principles of legislative drafting in the preparation of budget bills. One of the principles of legislative drafting is the observance of preemptive clarification rules. With the specification of Clause 9 of the mentioned general policy, the budget laws from the year 1398 onwards must be drafted and approved in accordance with the preemptive clarification rules. The question of this paper is whether legislation within the budget, through the approval of provisions and notes of the budget, is being conducted correctly from the perspective of preemptive clarification rules and legislative principles. Furthermore, what impact does the non-approval of provisions (notes and not figures or tables) of the budget law, while adhering to preemptive clarification rules, have on the current laws of the country and the legal system? In this research, using a descriptive-analytical method and for the first time, by examining the provisions of the budget laws of the country from 1399 to 1402 in terms of clarification rules, we conclude that, on one hand, the lack of attention to the clarifying effects of budget laws on other current laws has become an incorrect practice, and on the other hand, the non-observance of clarifying principles and legislative rules poses a serious obstacle to achieving an optimal legal system. Budget provisions must be prepared and approved in accordance with preemptive clarification rules; otherwise, the public rights and judicial security of the people are threatened due to the emergence of conflicting interpretations by executive and judicial authorities.